Effect of total replacement of fishmeal by earthworm and Azolla filiculoides meals in the diets of Nile tilapia Oreochromis niloticus (Linnaeus, 1758) reared in concrete tanks - Djissou, Arnauld S. M.; Ochiai, Akito; Koshio, Shunsuke; Fiogbe, Emile D. (Indian Journal of Fisheries, 2017)
In order to eliminate use of fishmeal in aquafeeds, we evaluated the effect of total replacement of fish meal by a mixture of earthworm (Eisenia foetida) and aquatic fern Azolla filiculoides in the diets of Nile tilapia Oreochromis niloticusÂ (Linnaeus, 1758). The experiment was conducted in O. niloticus fingerlings (initial mean weight = 5.6Â±0.2 g) for a period of 60 days. Five experimental diets isoproteic (30.4Â±0.6% protein) comprising control diet A0 and four test diets (A1 to A4) without fish meal were formulated. To satisfy essential amino acids requirements in test diets, the ratios 2:1; 1:1; 1:2; 1:5 between A. filiculoides and earthworm meals were used respectively in total replacement of fish meal. The diets were tested in triplicate. On termination of the experiment, the final mean weights in the test diets (10.79 to 11.94 g) were lower than 14.9 g obtained in group fed control diet (p<0.05). The best growth performance and feed utilisation were obtained in fish fed test diets A1 and A4 (SGR = 1.25 and 1.26% day-1; FCR = 2.37 and 2.31 respectively). Excess of lysine in test diets was found to affect the feed utilisation.